Primary Neuroendocrine Carcinoma of the Transverse Colon - Erginöz, Ergin; Nakashidze, Marika; Yüceyar, Necip Serdar; Pekmezci, Salih; Ertürk, Murat Süphan (Cerrahpaşa Medical Journal, 2022)
Neuroendocrine tumors are the proliferation of neuroendocrine cells that are known to be highly aggressive with a high mortality rate. The vast majority are seen within the small intestine and rectum. Rarely, within the colon, they are observed in the cecum or the ascending colon. In this case, a 66-year-old woman presented to the clinic with chronic fatigue and constipation. Work-up of the patient led to the diagnosis of an ulcerating mass within the mid-transverse colon, a highly unlikely location, where the biopsy revealed neuroendocrine carcinoma. Extended right hemicolectomy and ileotransversostomy were performed, and the pathological report was consistent with primary neuroendocrine carcinoma. These tumors are usually observed in the elderly population and are detected at an advanced stage. Routine colonoscopic examinations should therefore be performed for early diagnosis and management. Cite this article as: Erginöz E, Nakashidze M, Yüceyar NS, Pekmezci S, Ertürk MS. Primary neuroendocrine carcinoma of the transverse colon. Cerrahpaşa Med J. 2023;47(1):105-107.